Teaching Readiness of Newly Deployed Public School Elementary Teachers in the Northern Districts of Nueva Vizcaya: An Assessment - Bacud, Keenevie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the teaching readiness of newly deployed public elementary school teachers in the Northern Districts of Nueva Vizcaya. Guided by the Input–Process–Output (IPO) Model, it examined pedagogical knowledge and skills, classroom management, curriculum knowledge, professional attitude and emotional readiness, factors that hinder teaching readiness, and the support systems available to newly deployed teachers. A descriptive research design, specifically a descriptive survey, was employed. Data were collected using a researcher-made, validated questionnaire administered to purposively selected newly deployed public elementary school teachers. The data were analyzed using frequency, percentage, and weighted mean. The findings revealed that the respondents demonstrated a very evident level of teaching readiness across all measured dimensions, with curriculum knowledge obtaining the highest level of readiness. The teachers exhibited competence in instructional planning, classroom management, curriculum implementation, and professional attitude and emotional readiness. The factors that hindered teaching readiness were generally perceived as slightly serious, with classroom management, limited instructional resources, infrastructure, workload, and curriculum adaptation identified as the primary challenges. Institutional support systems, including mentoring, coaching, seminars and trainings, instructional supervision, and collaborative learning, were likewise found to be very evident, contributing to the teachers’ professional growth and instructional effectiveness. The study concludes that newly deployed teachers possess a high level of teaching readiness despite manageable professional challenges and recommends strengthening teacher induction, mentoring, continuous professional development, instructional support, and performance feedback to further enhance teaching competence. The study supports Sustainable Development Goal (SDG) 4 – Quality Education and SDG 8 – Decent Work and Economic Growth by promoting teacher competence, continuous professional development, and supportive learning environments. It contributes to educational, institutional, community, and socio-economic sustainability by providing evidence to strengthen teacher preparation, professional support systems, and instructional quality in basic education.